Experimental analysis of crack evolution in concrete by the acoustic emission technique - J. Saliba; A. Loukili; J.P. Regoin; D. Grégoire; L. Verdon; G. Pijaudier-Cabot (Fracture and Structural Integrity)
The fracture process zone (FPZ) was investigated on unnotched and notched beams with different notch depths. Three point bending tests were realized on plain concrete under crack mouth opening displacement (CMOD) control. Crack growth was monitored by applying the acoustic emission (AE) technique. In order to improve our understanding of the FPZ, the width and length of the FPZ were followed based on the AE source locations maps and several AE parameters were studied during the entire loading process. The bvalue analysis, defined as the log-linear slope of the frequency-magnitude distribution of acoustic emissions, was also carried out to describe quantitatively the influence of the relative notch depth on the fracture process. The results show that the number of AE hits increased with the decrease of the relative notch depth and an important AE energy dissipation was observed at the crack initiation in unnotched beams. In addition, the relative notch depth influenced the AE characteristics, the process of crack propagation, and the brittleness of concrete.